Coexistence, Classroom Climate and Philosophy for Children - Gonzalo Romero Izarra; Amparo Caballero González (Revista Electrónica Interuniversitaria de Formación del Profesorado)
In this paper we analyse the relationship between the classroom’s social climate and the general climate of society in which the school is inserted. We consider essential to start from this reflection in order to define an educational process for social transformation. Philosophy for Children is a methodological option to improve this social climate as it offers teachers and pupils a potentially transforming work that deepens into the values of human relationships for people who are concerned with what happens around them. These are the foundations for democratic relations and a positive classroom social climate.